2013
DOI: 10.1186/1467-4866-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline decomposition of synthetic jarosite with arsenic

Abstract: The widespread use of jarosite-type compounds to eliminate impurities in the hydrometallurgical industry is due to their capability to incorporate several elements into their structures. Some of these elements are of environmental importance (Pb2+, Cr6+, As5+, Cd2+, Hg2+). For the present paper, AsO43- was incorporated into the lattice of synthetic jarosite in order to carry out a reactivity study. Alkaline decomposition is characterized by removal of sulfate and potassium ions from the lattice and formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The density of ammonium−arsenic jarosite was determined with a picnometer, using distilled water as immersion liquid. The result was 2.72 g cm −3 , which is similar to the values reported in previous studies on jarosite type compounds with arsenic [11,13,15] and ammonium jarosite with silver [10], as shown on Table 2. Table 2.…”
Section: Synthesis and Characterizationsupporting
confidence: 80%
See 1 more Smart Citation
“…The density of ammonium−arsenic jarosite was determined with a picnometer, using distilled water as immersion liquid. The result was 2.72 g cm −3 , which is similar to the values reported in previous studies on jarosite type compounds with arsenic [11,13,15] and ammonium jarosite with silver [10], as shown on Table 2. Table 2.…”
Section: Synthesis and Characterizationsupporting
confidence: 80%
“…In a recent study on the decomposition of an arsenic-containing jarosite compound in alkaline media [11,12], it was found that arsenic remained in the decomposition product, mainly as a constituent of amorphous iron hydroxide. There are few works on the dissolution and stability of such compounds, making the data insufficient for evaluating the real environmental risk caused by the improper disposal of the generated precipitates [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are kinetic stability studies of jarosite−type compounds containing toxic metals such as arsenic, chromium and lead in alkaline medium such as NaOH and Ca(OH) 2 . These studies determine that the decomposition of jarosite−type compounds is closely related to the reaction conditions, mainly the temperature and the pH of the reaction medium . The contribution of this work is to document the behavior of the mercury contained in a synthetic jarosite in sodium hydroxide medium, by examining the reaction nature, providing information on the kinetic model, the controlling stage of the decomposition process and the reaction stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, there is no proper diffusion of OH − ions into the interface between the ash layer and the unreacted core. 38,46 X-ray diffraction analysis shows the gradual decomposition of the synthetic solid, which becomes amorphous at a reaction time of 140 min and a concentration of Ca(OH) = 1.4 g L −1 are shown in Figure 6. The residual solid is most probably composed of iron hydroxide with weakly adsorbed CrO 4 2− .…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…45,46 If the rate of the chemical reaction is slow compared to that of the transport of matter, equation 5 defines the behavior of the reaction:…”
Section: Synthesis and Characterizationmentioning
confidence: 99%